Formation of a small impact structure discovered within the Agoudal meteorite strewn field, Morocco. (21st December 2014) - Lorenz, C. A.; Ivanova, M. A.; Artemieva, N. A.; Sadilenko, D. A.; Chennaoui Aoudjehane, H.; Roschina, I. A.; Korochantsev, A.V.; Humayun, M.
Abstract A relic impact structure was recognized within the strewn field of the Agoudal iron meteorite. The heavily eroded structure has preserved shatter cones in a limestone basement, and remnants of autochthonous and allochthonous breccias. Fragments of iron incorporated into the allochthonous breccia have a chemical composition (Ni = 5.16 wt%, Ir = 0.019 ppm) similar to that of the Agoudal meteorite, supporting a syngenetic origin of the strewn field and the impact structure. The total recovered mass of Agoudal meteorite fragments is estimated at approximately 500 kg. The estimated size of the SE–NW‐oriented strewn field is 6 × 2 km. Model calculations with minimal preatmospheric size show that a similar meteorite strewn field plus one small crater with observed shock effects could be formed by fragmentation of a meteoroid approximately 1.4 m in diameter with an impact angle of approximately 60° from the horizontal. However, the most probable is an impact of a larger, 3–4 m diameter meteoroid, resulting a strewn field with approximately 10 craters, 10–30 m in diameter each, plus numerous meteorite fragments. The calculated scattering area of meteorite shrapnel ejected from these impact craters could completely cover the observed strewn field of the Agoudal meteorite.